Highly dexterous 2‐module soft robot for intra‐organ navigation in minimally invasive surgery. Issue 1 (5th December 2017) - Abidi, Haider; Gerboni, Giada; Brancadoro, Margherita; Fras, Jan; Diodato, Alessandro; Cianchetti, Matteo; Wurdemann, Helge; Althoefer, Kaspar; Menciassi, Arianna
Abstract: Background: For some surgical interventions, like the Total Mesorectal Excision (TME), traditional laparoscopes lack the flexibility to safely maneuver and reach difficult surgical targets. This paper answers this need through designing, fabricating and modelling a highly dexterous 2‐module soft robot for minimally invasive surgery (MIS). Methods: A soft robotic approach is proposed that uses flexible fluidic actuators (FFAs) allowing highly dexterous and inherently safe navigation. Dexterity is provided by an optimized design of fluid chambers within the robot modules. Safe physical interaction is ensured by fabricating the entire structure by soft and compliant elastomers, resulting in a squeezable 2‐module robot. An inner free lumen/chamber along the central axis serves as a guide of flexible endoscopic tools. A constant curvature based inverse kinematics model is also proposed, providing insight into the robot capabilities. Results: Experimental tests in a surgical scenario using a cadaver model are reported, demonstrating the robot advantages over standard systems in a realistic MIS environment. Conclusion: Simulations and experiments show the efficacy of the proposed soft robot.